Effect of thermal treatment on the optical and the structural properties of In0.5Ga0.5As quantum dots - Shin, Jae Cheol; Choi, Won Jun; Choe, Jeong-Woo (KOREAN PHYSICAL SOC, 2014)
The optical and the structural properties of a 3-stacked In0.5Ga0.5As quantum dot (QD)/GaAs structure subjected to a post thermal annealing process have been investigated. Photoluminescence (PL) and time-resolved PL spectroscopy have been performed to examine the optical properties of the as-grown and thermally-treated QD structures. Thermal annealing of the QD structure at temperatures up to 700 A degrees C leads to enhancements of the PL intensity and the carrier decay time without any PL peak shifts. The increases in the PL intensity and the carrier lifetime can be attributed to a reduction in the number of crystal defects in the QDs and in the GaAs layer near the QDs. The structural properties of the In0.5Ga0.5As QDs/GaAs heterointerface have been further examined with a transmission electron microscope analysis.
Keywords: MOLECULAR-BEAM EPITAXY; CARRIER LIFETIMES; LAYER; GROWTH; WELL